Three-Year-Olds Solved a Mental Rotation Task Above Chance Level, but No Linear Relation Concerning Reaction Time and Angular Disparity Presented Itself - Krüger, Markus (Frontiers in Psychology, 2018)
Three-year-olds and 4-year-olds have severe difficulties solving standard mental rotation tasks. Only 5-year-olds solve such tasks above chance reliably. In contrast studies relying on simplified mental rotation tasks indicate that infants discriminate between an object and its mirror image. Furthermore in another simplified mental rotation task with 3-year-olds, a linear relation between angular disparity and reaction time typical for mental rotation was revealed. Therefore it was assumed that 3-year-olds’ capabilities are underestimated. In the current study, 3-year-olds were trained in two isolated sessions to solve standard mental rotation tasks and were tested in a third session. Three-year-olds solved this test above chance as a group - a substantial number of them doing so on an individual level. However, a linear relation between angular disparity and reaction time, that would indicate an analogue mental transformation, was not discernable. Nevertheless, these findings are in accordance with a continuous line describing mental rotation in infants and older children. And, these also indicate that children’s mental rotation capabilities might be underestimated.